Pengembangan Passive Infrared Sensor (PIR) HC-SR501 dengan Microcontrollers ESP32-CAM Berbasiskan Internet of Things (IoT) dan Smart Home sebagai Deteksi Gerak untuk Keamanan Perumahan - Ade Irma Purnamasari; Andi Setiawan (Prosiding SISFOTEK, 2019)
HC-SR501 passive infrared sensor (PIR) is a sensor to detect the motion of an object that works when the object crosses the area or the vertex of the sensor, while ESP32-CAM is a microcontroller that works when given instructions by a programmer through the Arduino IDE editor. Both will work perfectly if given an ip address accompanied by Wi-Fi support to access it through internet media or known as an internet based things (IoT) smart home. The hardware is used in this study as a tool to detect housing security, especially housing in Perum Bumi Arumsari Sumber Cirebon District, most of the residents of the housing activities during the daytime. Technically both hardware will work optimally when the HC-SR501 passive infrared sensor (PIR) is connected via the ESP32-CAM microcontroller in charge of sending images or video, when the radius of the HC-SR501 passive infrared sensor (PIR) containing infrared radiation through Fresnel lenses and containing thermal energy regarding the pyroelectric sensor are met. Then the images or videos sent through ESP32-CAM that have been previously programmed through the Arduino IDE, are connected via Wi-Fi and received through a smartphone belonging to the householder to get a response to the results of the detection of HC-SR501 passive infrared sensor (PIR) and ESP32- CAM. The results obtained from this study are the effective distance from the HC-SR501 passive infrared sensor when the human detector is 0 meters to 5 meters, ESP32-CAM will send pictures or videos which means there are indications of thieves or unknown persons entering the house. Whereas at a distance of more than 5 meters, the HC-SR501 passive infrared sensor does not send images which means safe.